2016
DOI: 10.2174/1872312810666151223103353
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Confirmation that the Selective JAK1 Inhibitor Filgotinib (GLPG0634) has a Low Liability for Drug-drug Interactions

Abstract: the collective in vivo and in vitro data on drug-metabolizing enzymes and on key drug transporters, support co-administration of filgotinib with commonly used RA drugs to patients without the need for dose adjustments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…After oral administration, Filgotinib is metabolized to an active metabolite form which is Jak1 selectivity inhibitor (Namour et al, 2015). The main enzyme(s) that are involved in the metabolism of filgotinib are carboxylesterase1 (CES1) and carboxylesterase2 (CES2), which are localized mainly in the liver and intestine, respectively (Namour, 2015; Namour et al, 2016). It has been shown that CES2 is the major enzyme accountable for the formation of its active metabolite and CES1 could also form the active metabolite (Namour et al, 2016).…”
Section: Clinical Developmentsmentioning
confidence: 99%
“…After oral administration, Filgotinib is metabolized to an active metabolite form which is Jak1 selectivity inhibitor (Namour et al, 2015). The main enzyme(s) that are involved in the metabolism of filgotinib are carboxylesterase1 (CES1) and carboxylesterase2 (CES2), which are localized mainly in the liver and intestine, respectively (Namour, 2015; Namour et al, 2016). It has been shown that CES2 is the major enzyme accountable for the formation of its active metabolite and CES1 could also form the active metabolite (Namour et al, 2016).…”
Section: Clinical Developmentsmentioning
confidence: 99%
“…Filgotinib (GLPG0634/GS-6034) is a potent and selective inhibitor of JAK1,7 which is currently under investigation for the treatment of RA and inflammatory bowel disease 7–10. The efficacy and safety of filgotinib in patients with RA has previously been investigated in two short-term phase IIa studies, as add-on treatment to MTX, which suggested that filgotinib has the potential to be effective when administered as a once-daily dosing regimen .…”
Section: Introductionmentioning
confidence: 99%
“…Filgotinib and its metabolite are not substrates of cytochrome P450 or major drug transporters, with the exception of P-glycoprotein, and neither food nor acid-reducing agents have clinically relevant effects on their PK. 8,10 Neither moderate hepatic impairment nor mild-tomoderate renal impairment significantly impact the PK of filgotinib. 7,16,17 The increase in C max of filgotinib (2.1-fold) and metabolite (1.9-fold) with increasing the dose from 200 to 450 mg was greater than the anticipated C max increase that would take place as a result of drug-drug interactions or organ dysfunction in the target patient population, supporting the appropriateness of selecting 450 mg as the supratherapeutic dose for evaluation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…6 Filgotinib is primarily metabolized by carboxylesterase isoform 2, resulting in the loss of the cyclopropyl carboxylic acid group and formation of its major, circulating metabolite, which is predominantly excreted in the urine (>80%). 7,8 The metabolite also exhibits selective JAK1 inhibition, with approximately 16-to 20-fold higher exposure and longer half-life (23-27 hours for the metabolite versus 5-6 hours for filgotinib) but ß19-fold lower potency than filgotinib. 7,9,10 In phase 2 studies, filgotinib has shown clinical efficacy, rapid onset of activity, and a favorable safety and tolerability profile both as monotherapy and in combination with methotrexate in subjects with moderate to severe rheumatoid arthritis, [11][12][13] and in subjects with moderate to severe Crohn's disease.…”
mentioning
confidence: 99%